Analytical and clinical validation of pairwise microRNA expression analysis to identify medullary thyroid cancer in thyroid fine‐needle aspiration samples. Issue 3 (5th October 2020) - Ciarletto, Andrea M.; Narick, Christina; Malchoff, Carl D.; Massoll, Nicole A.; Labourier, Emmanuel; Haugh, Keith; Mireskandari, Alidad; Finkelstein, Sydney D.; Kumar, Gyanendra
Abstract : Background: Medullary thyroid carcinoma (MTC) is an aggressive malignancy originating from the parafollicular C cells. Preoperatively, thyroid nodule fine‐needle aspiration cytology (FNAC) and pathogenic gene mutations are definitive in approximately one‐half of cases. MicroRNAs (miRNAs) are endogenous, noncoding, single‐stranded RNAs that regulate gene expression, a characteristic that confers the potential for identifying malignancy. In the current study, the authors hypothesized that differential pairwise (diff‐pair) analysis of miRNA expression levels would reliably identify MTC in FNA samples. Methods: The relative abundance of 10 different miRNAs in total nucleic acids was obtained from ThyraMIR test results. Diff‐pair analysis was performed by subtracting the critical threshold value of one miRNA from the critical threshold values of other miRNAs. Next‐generation sequencing with the ThyGeNEXT panel identified oncogenic gene alterations. The discovery cohort consisted of 30 formalin‐fixed, paraffin‐embedded benign and malignant thyroid neoplasms, including 4 cases of MTC. After analytical validation, clinical validation was performed using 3 distinct cohorts (total of 7557 specimens). Results: In the discovery cohort, 9 diff‐pairs were identified as having significant power using the Kruskal‐Wallis test ( P  < .0001) to distinguish MTC samples from non‐MTC samples. The assay correctly classified all MTC and non‐MTC samples in the analytical validation study and in the 3 clinical validation cohorts. The overall test accuracy was 100% (95% confidence interval, 99%‐100%). In indeterminate FNAC samples, the sensitivity of the diff‐pair analysis was greater than that of the MTC‐specific mutation analysis (100% vs 25%; P  = .03). Conclusions: Pairwise miRNA expression analysis of ThyraMIR results were found to accurately predict MTC in thyroid FNA samples, including those with indeterminate FNAC findings. Abstract : The authors have developed and validated a microRNA (miRNA) test for the detection of medullary thyroid cancer (MTC) in preoperative thyroid nodule samples. The method, based on differential pairwise analysis of miRNA expression data generated using the ThyraMIR Thyroid miRNA Classifier, accurately predicts MTC with 100% sensitivity and 100% specificity in thyroid fine‐needle aspiration biopsies.